Solubility of Quercetin in Wines - Lanati, Donato; Cascio, Patrizia; Pollon, Matteo; Corona, Onofrio; Marchi, Dora (South African Journal of Enology and Viticulture, 2022)
Quercetin solubility at 18 °C and 0 °C was determined in an hydroalcoholic buffer solution with pH 3.20 and in four Italian wines to study the formation of quercetin precipitate mechanism in wines. The wines selected were Barbera 2018 for the typically high content in bisulfite bleachable pigments, red Cirò 2014, for its typically high content of flavonoids, Sangiovese 2014, for the presence of quercetin deposits in bottle, and white Cirò 2018, for the absence of red pigments. All the samples were spiked with 30 mg/L quercetin. The amount of quercetin solubilized at 18 °C and 0 °C in the hydroalcoholic buffer was much lower than in wines, while that solubilised in Barbera was much higher compared to red Cirò, Sangiovese and white Cirò. Solubilised quercetin was lower in all wine samples stored at 0 °C than in those at 18 °C. The pigment composition of the three red wines examined suggested that the over-solubility of quercetin could be due to the formation of soluble co-pigmentation complexes between quercetin and monomer anthocyanins and/or bisulphate-bleachable flavanol-anthocyanin pigments. A positive correlation between quercetin solubility and bleachable pigment was noted: the richer the wine in bleachable pigments, the higher the solubility of quercetin. Quercetin haze formation appeared due to the release of quercetin from co-pigmentation complexes during wine maturation and storage ,as its counterpart, anthocyanins, form non-bleachable pigments or are degraded in hydrolytic or oxidation reactions. Quercetin in aged red wines seemed to reach a content similar to that of white wine spiked with quercetin. Nevertheless, the quercetin content of aged red wines in which a quercetin haze has been found could be lower than that when added white wine, due to its degradation probably being induced by oxidation reactions. Finally, the solubilized quercetin content in white Cirò, which was higher than the hydroalcoholic buffer solution, suggested that there may be different substances in wines than pigments that prevent the growth of quercetin crystals. However, their nature was not determined in this study.